How and when Alphanumeric Brand Names Affect Consumer Preferences - Gunasti, Kunter; Ross, William T. (Journal of Marketing Research, 2010)
This research develops a taxonomy of alphanumeric brand names (ABs) based on the alignment between the brand names and their links to products and attributes. Five empirical studies reveal that ABs have systematic effects on consumers’ product choices, moderated by consumers’ need for cognition, the availability of product attribute information, and the taxonomic category of the AB. In an identical choice set, the choice share of a product option whose brand name takes a higher versus lower numeric portion (e.g., X-200 versus X-100) increases, and it is preferred more even when it is objectively inferior to other choice alternatives. Consumers with low need for cognition use “the higher, the better” heuristic to select options labeled with ABs and choose brands with higher numeric portions. Consumers with high need for cognition process ABs more systematically and make inferences about attribute values based on brand name–attribute correlations. The effects of ABs on consumer preferences are prevalent for most technical products, even when consumers do not know the product category or meanings of attributes.